Role of BACH1 in multiple myeloma - Yan Chen; Zhiyong Zeng; Junmin Chen (Hematology)
Objective Examine Bach1 protein expression in bone marrow biopsy specimens obtained from newly diagnosed multiple myeloma (NDMM) and iron deficiency anemia (IDA) patients. Conduct a thorough analysis to explore the potential connection between Bach1 and the onset as well as treatment response of NDMM.Methods This study investigated Bach1 expression in bone marrow biopsy tissues from NDMM and IDA patients. Immunohistochemical staining and Image-pro Plus software were utilized for quantitatively obtaining the expression level of Bach1 protein. Arrange Bach1 expression levels from high to low, and use its median expression level as the threshold. Samples with Bach1 expression level above the median are categorized as the high-expression group, while those below the median are categorized as the low-expression group. Under this grouping, a detailed discussion was conducted to explore relationship of the Bach1 expression level with the patients’ gender, ISS stage, and survival rate based on the Bortezomib (Btz) therapy.Results Our experiment indicates that the expression level of Bach1 in NDMM patients is significantly higher than in IDA patients. Furthermore, we discovered that patients in the high-expression group exhibit better prognosis compared to those in the low-expression group after Btz-treatment. Bioinformatics analysis further confirms this conclusion.Conclusion By categorizing Bach1 expression level as high and low, our study offers a unique perspective on understanding the relationship between Bach1 and NDMM.